Real-time 3D sound system with head tracking - Zhang, Zongyang. (2013)
Due to the increasing prevalence of 3D movies and 3D gaming, there is a corresponding demand among the consumers for a better listening environment while playing 3D games or watching 3D movies. Nowadays, the usage of headphone is rather popular in order to create a more desirable and personal sound field for consumers. Nonetheless, the anticipated sound scene normally moves with the end user while listening to the earphone. This is not in line with the actual experience in our daily life. With the monitoring of the head movement, it is possible to reduce this disparity by connecting the head-motion sensors to the earphone.